The Role of Community Education in the Field of Traffic (Dikmas Lantas) Education and Engineering Unit (Dikyasa) in Preventing Traffic Violations of High School Students at the Magelang Police Department - Dhira, Bagus Satya (Advances in Police Science Research Journal, 2020)
This research uses a qualitative approach. Data collection techniques used were interviews, observation and document study. Research location in Magelang Police jurisdiction. The results of the study showed that the violations of high school student traffic at the Magelang Police Station were classified as high. The role of the Dikmas Lantas Dikyasa Unit in preventing violations of high school student traffic violations at the Magelang Police Station is to become a ceremonial coach, carrying out counseling activities, safety riding, and appeals through zebra heroines. Factors that influence the Role of Public Relations Then Dikyasa Unit, namely, Man, Money, Method, Materials, Machine and Markets. The research concluded that the high traffic violations of high school students are influenced by five factors. The role of the Dikmas Lantas Dikyasa Unit in preventing high school student traffic violations at the Magelang Police Station was not optimal because the traffic violations of high school students were still relatively high in 2014 to 2016. The implementation of the Dikmas Lantas Unit in the Magelang Police Precinct in accordance with the Job Description Unit Dikyasa. There are factors that become obstacles and supporters that influence the role of the Board of Education Board of Magelang Regional Police Unit. Suggestions, sanctions for traffic violators are emphasized, expanding the target of the Board of Directors of All High Schools in Magelang, improving the ability of personnel through Education and Training, fulfilling the budget and Sarpras supporting the role of the Unit Dikyasa and giving rewards to the Dikmas Lantas activities.